A comparative study of special educator preparation in Norway and Sweden. (22nd October 2018) - Cameron, David Lansing; Tveit, Anne Dorthe; Jortveit, Maryann; Lindqvist, Gunilla; Göransson, Kerstin; Nilholm, Claes
Abstract : The purpose of this study was to explore similarities and differences between special educator preparation in Norway and in Sweden. Graduates of special education programmes at two Norwegian ( n = 320) and two Swedish universities ( n = 425) who completed their training between 2001 and 2012 responded to surveys. Findings indicate that both Swedish and Norwegian graduates felt prepared for their current work and that teaching approaches employed in the different programmes were similar. However, there appears to be a stronger focus on pupils' social goals in Sweden, as well as on advising teachers, school development and promoting inclusive environments. In contrast, Norwegian participants reported a greater focus on preparation to work with specific types of learning and behavioural difficulties. Findings are discussed in relation to differing political and social structures, such as national regulations for steering special educator preparation in Sweden, which are absent in the Norwegian context.